Childhood multisystem inflammatory syndrome associated with COVID-19 (MIS-C): a diagnostic and treatment guidance from the Rheumatology Study Group of the Italian Society of Pediatrics - Marco Cattalini; Andrea Taddio; Claudia Bracaglia; Rolando Cimaz; Sara Della Paolera; Giovanni Filocamo; Francesco La Torre; Bianca Lattanzi; Alessandra Marchesi; Gabriele Simonini; Gianvincenzo Zuccotti; Fiammetta Zunica; et al. (BMC, 2021)
Abstract Background Italy was the first Western country to be hit by the SARS-CoV-2 epidemic. There is now mounting evidence that a minority of children infected with SARS-CoV2 may experience a severe multisystem inflammatory syndrome, called Multisystem inflammatory Syndrome associated with Coronavirus Disease 2019 (MIS-C). To date no universally agreed approach is available for this disease. Main body as Italy is now facing a second hity of COVID-19 cases, we fear a recrudescence of MIS-C cases. We have, therefore, decided to prepare a report that will help clinicians to face this novel and challenging disease. We propose a diagnostic algorithm, to help case definition and guide work-up, and a therapeutic approach. MIS-C should be promptly recognized, based on the presence of systemic inflammation and specific organ involvement. Early treatment is crucial, and it will be based on the combined use of corticosteroids, high-dose immunoglobulins and anti-cytokine treatments, depending on the severity of the disease. Ancillary treatments (such as. aspirin and thrombo-profilaxis) will be also discussed. Conclusions we propose a document that will help physicians to diagnose and treat MIS-C patients. Given the level of evidence available and the methodology used, this document should not be interpreted as a guideline; the final decision about the optimal management should still be taken by the caring physician, on an individual basis.